Whole-genome analysis of an aggressive metastatic pancreatic solid pseudopapillary neoplasm - Phoebe T. M. Cheng; James T. Topham; Ayman Aldeheshi; Gregory A. Taylor; Erin Pleasance; Melissa K. McConechy; Jessica M. T. Nelson; David F. Schaeffer; Steven J. M. Jones; Marco A. Marra; Janessa Laskin; Daniel J. Renouf (npj Precision Oncology)
Abstract Pancreatic solid pseudopapillary neoplasms (SPNs) are uncommon tumors that rarely exhibit aggressive behavior. Given disease rarity, comprehensive studies to understand tumor biology, clinical course, and optimal management are limited. We describe an unusual case of a 55-year-old man with metastatic pancreatic SPN, where whole-genome and transcriptome analyses of the primary tumor and a metastatic liver lesion revealed a shared homozygous non-canonical mutation in APC. The patient received upfront modified FOLFIRINOX (infusional 5-fluorouracil, irinotecan, and oxaliplatin) chemotherapy due to rapidly progressive symptoms, demonstrating an early and sustained treatment response. Therefore, we identified potential genetic determinants of tumorigenesis and progression in a pathologically and clinically aggressive SPN, which may have important prognostic and treatment implications.